2020
DOI: 10.1177/0300060520936053
|View full text |Cite
|
Sign up to set email alerts
|

Chidamide combined with ibrutinib improved the prognosis of primary bone marrow diffuse large B cell lymphoma

Abstract: Primary bone marrow diffuse large B cell lymphoma (DLBCL) is an independent pathologic type with a poor prognosis when treated with standard chemoimmunotherapy. Generally, rituximab-based high-dose chemotherapy regimens such as dose-adjusted etoposide, prednisone, vincristine, cyclophosphamide, and doxorubicin (DA-EPOCH) can be administered to young patients, followed by autologous stem cell transplantation. For elderly patients, the rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The regimen was well tolerated and the patient again achieved remission. Similarly, it was reported that combination treatment with chidamide and ibrutinib produced complete remission in a patient with primary refractory DLBCL (12). Nevertheless, the mechanism underlying the synergistic mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The regimen was well tolerated and the patient again achieved remission. Similarly, it was reported that combination treatment with chidamide and ibrutinib produced complete remission in a patient with primary refractory DLBCL (12). Nevertheless, the mechanism underlying the synergistic mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 94%
“…Zanubrutinib, a second-generation BTKi, produced an ORR of 29% and a CR rate of 17% in R/R DLBCL regardless of molecular subtype (11). In preclinical experiments and case reports, dual inhibition of HDAC and BTK showed a possible synergistic effect for DLBCL (12,13).…”
Section: Introductionmentioning
confidence: 97%
“…There were 51 high-grade BCL cases, and among these 77% (48/62) were DLBCL and 5% (3/62) were left unclassifiable. 1,3,5-33 Meanwhile, there were 11 cases of low-grade BCL, and 11% (7/62) were FLs. 1,34,35 According to the character of our case, we focused more on the analysis of HGBL.…”
Section: Discussionmentioning
confidence: 99%